Purification and Biochemical Characterization of Taxadiene Synthase from Bacillus koreensis and Stenotrophomonas maltophilia - Ashraf S. A. El-Sayed; Maher Fathalla; Ahmed A. Shindia; Amgad M. Rady; Ashraf F. El-Baz; Yara Morsy; Basel Sitohy; Mahmoud Sitohy (MDPI AG, 2021)
Taxadiene synthase (TDS) is the rate-limiting enzyme of Taxol biosynthesis that cyclizes the geranylgeranyl pyrophosphate into taxadiene. Attenuating Taxol productivity by fungi is the main challenge impeding its industrial application; it is possible that silencing the expression of TDS is the most noticeable genomic feature associated with Taxol-biosynthetic abolishing in fungi. As such, the characterization of TDS with unique biochemical properties and autonomous expression that is independent of transcriptional factors from the host is the main challenge. Thus, the objective of this study was to kinetically characterize TDS from endophytic bacteria isolated from different plants harboring Taxol-producing endophytic fungi. Among the recovered 23 isolates, Bacillus koreensis and Stenotrophomonas maltophilia achieved the highest TDS activity. Upon using the Plackett-Burman design, the TDS productivity achieved by B. koreensis (18.1 µmol/mg/min) and S. maltophilia (14.6 µmol/mg/min) increased by ~2.2-fold over the control. The enzyme was purified by gel-filtration and ion-exchange chromatography with ~15 overall folds and with molecular subunit structure 65 and 80 kDa from B. koreensis and S. maltophilia, respectively. The chemical identity of taxadiene was authenticated from the GC-MS analyses, which provided the same mass fragmentation pattern of authentic taxadiene. The tds gene was screened by PCR with nested primers of the conservative active site domains, and the amplicons were sequenced, displaying a higher similarity with tds from T. baccata and T. brevifolia. The highest TDS activity by both bacterial isolates was recorded at 37-40 °C. The Apo-TDSs retained ~50% of its initial holoenzyme activities, ensuring their metalloproteinic identity. The activity of purified TDS was completely restored upon the addition of Mg2+, confirming the identity of Mg2+ as a cofactor. The TDS activity was dramatically reduced upon the addition of DTNB and MBTH, ensuring the implementation of cysteine-reactive thiols and ammonia groups on their active site domains. This is the first report exploring the autonomous robust expression TDS from B. koreensis and S. maltophilia with a higher affinity to cyclize GGPP into taxadiene, which could be a novel platform for taxadiene production as intermediary metabolites of Taxol biosynthesis.